2019
DOI: 10.1111/jels.12208
|View full text |Cite
|
Sign up to set email alerts
|

Damage Caps and Defensive Medicine: Reexamination with Patient‐Level Data

Abstract: Physicians often claim that they practice “defensive medicine,” including ordering extra imaging and laboratory tests, due to fear of malpractice liability. Caps on noneconomic damages are the principal proposed remedy. Do these caps in fact reduce testing, overall health-care spending, or both? We study the effects of “third-wave” damage caps, adopted in the 2000s, on specific areas that are expected to be sensitive to med mal risk: imaging rates, cardiac interventions, and lab and radiology spending, using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…27,38 Of the 15 studies that reported no significant associations between liability measures and mortality in the deterrence direction, 9 used tort reforms as the measure of liability risk and 6 used claim frequency, average payment per paid claim, jury awards, or other measures (Table 3). These studies were also diverse in the patient populations studied, ranging from narrowly defined disease groups (eg, patients who had bladder cancer, 17 patients who underwent cranial neurosurgery 33 ) to wide patient populations (eg, all Medicare patients 18,44 ). Two of the 3 studies that found limited evidence of deterrence used tort reforms as the measure of liability risk.…”
Section: Evidence Concerning Patient Mortalitymentioning
confidence: 99%
“…27,38 Of the 15 studies that reported no significant associations between liability measures and mortality in the deterrence direction, 9 used tort reforms as the measure of liability risk and 6 used claim frequency, average payment per paid claim, jury awards, or other measures (Table 3). These studies were also diverse in the patient populations studied, ranging from narrowly defined disease groups (eg, patients who had bladder cancer, 17 patients who underwent cranial neurosurgery 33 ) to wide patient populations (eg, all Medicare patients 18,44 ). Two of the 3 studies that found limited evidence of deterrence used tort reforms as the measure of liability risk.…”
Section: Evidence Concerning Patient Mortalitymentioning
confidence: 99%
“…A range of other studies, however, have failed to find evidence of any change in health-care utilization or spending in connection with variations in medical liability pressure. Included in this latter set of studies is Sloan and Shadle (2009), the Congressional Budget Office (2004), Paik et al (2017), and Moghtaderi et al (2017) (in each case drawing on damages caps and related reforms).…”
Section: Iia Defensive Medicine Background and Literature Reviewmentioning
confidence: 99%
“…(6) The study includes data from Europe. *USA,11 12 14 76–145 New Zealand,74 75 146 147 China,148–150 Japan,151 152 Iran,153 Israel,154–160 Sudan,161 Canada,162 163 Australia,164 165 South Africa,166 Singapore,167 India,168 Hong Kong,169 Brazil170 and one study from both USA, Canada and South Africa 73…”
Section: Resultsmentioning
confidence: 99%